Okul öncesi eğitim kurumuna devam eden 4-5 yaş grubu çocukların görsel algı gelişimlerine frostig gelişimsel görsel algı eğitim programının etkisi - (:unkn) unknown (My University, 2012)
Bu araştırmanın amacı, okul öncesi eğitim kurumuna devam eden 4-5 yaş çocukların görsel algı gelişimlerine Frostig Gelişimsel Görsel Algı Eğitim Programı nın etkisinin incelenmesidir. Araştırma ön test-son test kontrol gruplu deneme modeline uygun olarak gerçekleştirilmiştir. Araştırmanın çalışma grubunu okul öncesi eğitim kurumuna devam eden 161 deney, 161 kontrol olmak üzere toplam 322 çocuk oluşturmaktadır. Araştırmada Frostig Gelişimsel Görsel Algı Testi ve Frostig Gelişimsel Görsel Algı Eğitim Programı kullanılmıştır. Frostig Gelişimsel Görsel Algı Testi ve Eğitim Programında görsel algı becerileri; el-göz koordinasyonu, şekil-zemin algısı, şekil sabitliği algısı, mekan ile konum ilişkisi algısı ve mekânsal ilişkiler algısı başlıkları altında değerlendirilmektedir. Deney grubunda yer alan çocuklara 5 ay boyunca haftada iki gün Frostig Gelişimsel Görsel Algı Eğitim Programı uygulanmıştır. Frostig Gelişimsel Görsel Algı Eğitim Programı, çocukların devam ettikleri okul programının okuma-yazma hazırlık çalışmalarına dahil edilmiştir. Kontrol grubunda yer alan çocuklar ise normal okul programlarına devam etmişlerdir. Araştırma sonunda okul öncesi 4-5 yaş çocuklara görsel algılamayı destekleyici bir çalışmanın, çocukların görsel algılama becerilerini olumlu yönde etkilediği görülmüştür.

The purpose of this study is to investigate the effect of Frostig Developmental Program for Visual Perception on development of visual perception of 4-5 years old children who attended pre-school education institutions. The study was carried out in accordance with pre-test and post-test control group experimental design. The study group of the research was made from children ongoing pre-school education institutions. Totally 322 children were included in this study, 161of children were chosen as experimental group and 161 were chosen as control. Frostig Developmental Test of Visual Perception and Frostig Developmental Program for Visual Perception were used in this study. Visual perception skills in Frostig Developmental Test of Visual Perception and Training Programs were evaluated under the headings which were eye-motor coordination, figureground perception, perception of form constancy, perception of position in space and perception of spatial relationships. Frostig Developmental Program for Visual Perception was applied to the children in the experimental group as two days a week for 5 months. Frostig Developmental Program for Visual Perception was included in reading-writing preparatory studies of school curriculum for students in experimental group. The children in the control group continued their regular school programs. At the end of the research, it was seen that a study supporting visual perception for 4-5 aged pre-school children has positive effect on visual perception skills of children.
The effect of frostig developmental program for visual perception on development of visual perception of 4-5 years old children attending pre-school education institutions
Keywords: Eğitim, Eğitim Araştırmaları; Aile Çalışmaları